2015
DOI: 10.1186/s40555-014-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

Life history and DNA barcode of Oxyurella longicaudis (Birgei, 1910) (Cladocera, Anomopoda, Chydoridae)

Abstract: Background: Cladocera is an important group of freshwater zooplankton, and the species plays an important role in energy transfer and in aquatic food webs. Oxyurella longicaudis is a Chydoridae species that has been recorded in North and South America. The aim of this study is to investigate the life cycle aspects of parthenogenetic females of O. longicaudis cultured in laboratory under controlled conditions: temperature (23°C ± 05°C), photoperiod (12 h light/12 h dark), food supply, and reconstituted water. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 37 publications
7
10
0
Order By: Relevance
“…The average egg development time of 2.50 days for K. muelleri is within the range of variation found in the species cited by Castilho et al (2015). However, the fecundity of K. muelleri is lower compared with that of all the species reported previously.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The average egg development time of 2.50 days for K. muelleri is within the range of variation found in the species cited by Castilho et al (2015). However, the fecundity of K. muelleri is lower compared with that of all the species reported previously.…”
Section: Discussionsupporting
confidence: 78%
“…The r values obtained in this study indicated population growth between 15% to 24% per day, where the age of just one day for the first brood is relatively early compared with the revised data given by Castilho et al (2015) who reported that the age for the first brood was between 2.37 (Chydorus pubescens Sars, 1901) and5.73 days (Chydorus dentifer Daday, 1905). Ovalona kaingang (Sousa, Elmoor-Loureiro and Santos, 2015) was identified as Coronatella rectangula (Sars, 1861) by Viti et al (2013) and as Flavalona margipluma (Sousa, Santos, Güntzel, Diniz, Melo Junior and Elmoor-Loureiro, 2015) by Sousa and Elmoor-Loureiro (2019) (Alona iheringula in Santos- Silva et al 2014), and it had the first brood between 2.48 and 2.24 days.…”
Section: Discussionsupporting
confidence: 68%
“…The combination of longer life cycle and constant breeding may contribute to surpass periods of extreme variation of environmental conditions, ensuring the constant growth of the population. The short time that females of A. guttata survived after they stopped producing new eggs is similar to records for other species of cladocerans, such as Chydorus pubescens and Oxyurella longicaudis (Santos-Wisniewski et al, 2006;Almeida Castilho et al, 2015). Our study indicates that A. guttata presented a rapid body development, which suggests that this species allocates high amounts of energy to growth, to allow early reproduction in its life cycle.…”
Section: Maximum Days Of Life (Days) 37supporting
confidence: 87%
“…Cladocera covers approximately 700 species (Kotov et al, 2011) of which the Family Chydoridae is the most diverse. Within its subfamilies, Aloninae is the most speciose and recently is target of taxomomic studies as it includes cryptic speciation and species complexes previously defined (Elias-Gutierrez & Valdez-Moreno, 2008;Belyaeva & Taylor 2009;Castilho et al, 2015). Among them, the pulchella-group is composed of at least 17 species (Sinev, 2015), all of them named as Alona and considered as one of the most complex group (Sacherova & Hebert, 2003;Van Damme & Dumont, 2008).…”
Section: Introductionmentioning
confidence: 99%